2017
DOI: 10.11160/bah.57
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive monitoring of the fertilization rate in sea turtle nests: comparison between two techniques

Abstract: Egg fertilization rate is a defining event in the life history of oviparous species. However, for many terrestrial oviparous species, this parameter is only estimated after hatching and emergence of hatchlings, by studying evidence of embryonic development in unhatched eggs. We compared the accuracy of this method with a second technique based on the careful excavation of sea turtle nests within the first 96 hours of oviposition and calculating the proportion of alive eggs, where a clear white spot is external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…White spot formation did not indicate that individual eggs would develop successfully through to hatching; nearly all eggs formed white spots, even though there was reduced hatching success and higher early‐stage mortality in the hypoxic treatments. This provides further justification for monitoring white spot formation as a noninvasive method for estimating the fertilization rate for a clutch of eggs (Abella et al, 2017; Phillott et al, 2021; Phillott & Godfrey, 2020) because we found that the white spot still formed even when embryos died at early developmental stages. Based on our white spot formation data, at least 97% of eggs collected for our ex situ experiment were fertilized.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…White spot formation did not indicate that individual eggs would develop successfully through to hatching; nearly all eggs formed white spots, even though there was reduced hatching success and higher early‐stage mortality in the hypoxic treatments. This provides further justification for monitoring white spot formation as a noninvasive method for estimating the fertilization rate for a clutch of eggs (Abella et al, 2017; Phillott et al, 2021; Phillott & Godfrey, 2020) because we found that the white spot still formed even when embryos died at early developmental stages. Based on our white spot formation data, at least 97% of eggs collected for our ex situ experiment were fertilized.…”
Section: Discussionsupporting
confidence: 56%
“…After 3 days (3‐day hypoxia treatment) or 5 days (remaining three treatments), eggs were carefully removed from their Perspex chambers and placed in sand (7 ± 2% gravimetric water content) within normoxic incubators set to 30 ± 1°C. The eggs were monitored three times daily for the formation of the opaque white spot on the upper surface as an indication of development recommencing after oviposition (Abella et al, 2017). While the eggs were being removed from their chambers, two eggs from the hyperoxia treatment were inadvertently rotated.…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of unhatched eggs with no visible embryo ranged from 0% to 87% (mean ± sd = 15% ± 19). We have considered these indicative of early embryonic death, given the very high fertilization rate in the loggerhead turtle [ 54 ]. However, we cannot exclude that few of them were unfertile eggs since it is very difficult to discriminate between these two categories at the time of nest excavation, after approximately 2 months of decomposition [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have considered these indicative of early embryonic death, given the very high fertilization rate in the loggerhead turtle [ 54 ]. However, we cannot exclude that few of them were unfertile eggs since it is very difficult to discriminate between these two categories at the time of nest excavation, after approximately 2 months of decomposition [ 54 ]. Hatching success and the proportion of unhatched eggs with no visible embryo were strongly correlated (Spearman’s r s = −0.777, p -value < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…At egg laying, some fertilized eggs of sea turtles could have already died. Moreover, fertile eggs at laying have no external signals of embryonic development (Abella et al, 2017). Incubation temperature influences several factors in sea turtle egg incubation.…”
Section: Discussionmentioning
confidence: 99%